New earthworm records from Turkey, with description of three new species (Oligochaeta: Lumbricidae) - Szederjesi, Tímea; Pavlíček, Tomás; Coşkun, Yüksel; Csuzdi, Csaba (Zootaxa, 2014)
Identifying the earthworm material recently collected in different parts of Turkey (Marmara Region, Upper Mesopotamia, Hatay Province and East Anatolia) resulted in records of 29 earthworm species including three lumbricids new to science: Dendrobaena cevdeti, D. szalokii and Eisenia patriciae spp. nov. In addition, Dendrobaena cognettii is reported for the first time from the country. With this contribution, the number of earthworm species and subspecies registered in Turkey is raised to 80.